Cardiorespiratory fitness and development of childhood cardiovascular risk: The EXAMIN YOUTH follow-up study - Hauser, Christoph; Lichtenstein, Eric; Nebiker, Lukas; Streese, Lukas; Köchli, Sabrina; Infanger, Denis; Faude, Oliver; Hanssen, Henner (Frontiers in Physiology, 2023)
Background: Obesity-and hypertension-related cardiovascular (CV) risk has been shown to originate in childhood. Higher body mass index (BMI) and blood pressure (BP) have been associated with increased large artery stiffness and a lower microvascular arteriolar-to-venular diameter ratio (AVR) in children. This study aimed to investigate the association of cardiorespiratory fitness (CRF) with development of BMI, BP and vascular health during childhood.In our prospective cohort study, 1171 children aged 6 to 8 years were screened for CRF, BMI, BP, retinal vessel diameters and pulse wave velocity using standardized protocols.Endurance capacity was assessed by 20m shuttle run test. After 4 years, all parameters were assessed in 664 children using the same protocols.Results: Children with a higher CRF at baseline developed a significantly lower BMI (β [95% CI] -0.09 [-0.11 to -0.06] kg/m 2 , P < 0.001), a lower systolic BP (β [95% CI]-0.09 [-0.15 to -0.03] mmHg, P = 0.004) and a higher AVR (β [95% CI] 0.0004 [0.00004 to 0.0007] units, P = 0.027) after four years. The indirect association of CRF with development of retinal arteriolar diameters was mediated by changes in BMI.Our results identify CRF as a key modulator for the risk trajectories of BMI, BP and microvascular health in children. Obesity-related CV risk has been shown to track into adulthood, and achieving higher CRF levels in children may help counteract the development of CV risk and disease not only in pediatric populations, but may also help reduce the burden of CVD in adulthood.